Perspectivas metodológicas para a identificação do aboutness em textos narrativos de ficção - Moraes, João Batista Ernesto de [UNESP] (My University, 2012)
Proposal of a theoretical and methodological use of the generative meaning trajectory postulated by Greimas with the intention of developing a methodology for the identification of concepts in narrative texts of fiction to facilitate its subject indexing and classification.
Methodological perspectives for aboutness identification on fiction narrative texts
Keywords: Aboutness; Document analysis; Generative meaning trajectory; Narrative texts of fiction